Co‐production and adaptation of a prison‐based problem‐solving workbook to support the mental health of patients housed within a medium‐ and low‐secure forensic service - Amanda E. Perry; Heather Baker; Anne Aboaja; Lindsey Wilson; Sarah Morris; Patient Public Involved Service User (Wiley, 2024)
Abstract Introduction Problem‐solving skills (PSS) help to provide a systematic approach to dealing with and managing complex problems. The overall aim of this study was to assess the acceptability and feasibility of developing and adapting a prison‐based PSS  workbook for adults within a medium‐ and low‐secure hospital. Method We used the Medical Research Council framework in our participatory mixed methods study incorporating an adapted survey (to identify what types of problems people experience in secure hospitals), a series of three interactive workshops (to co‐produce two case study examples for a workbook) and we gathered feedback from patients and hospital staff on the acceptability and feasibility of the workbook. Data from the survey were used to inform the case study examples, and the feedback from patients and hospital staff was descriptively summarised and the results consolidated. Results In total, 82 (51%) patients took part in the survey; 22 patients and 49 hospital staff provided feedback on the workbook. The survey results indicated that patients regularly experience problems while in the hospital. Patients reported problems relating to restrictions of freedom and boredom. The workshops produced two case studies for the workbooks, with mainly positive patient and staff feedback. More work is required to improve the visual representation of the characters in the case studies, the amount and content of the language and the mechanism of the intervention delivery. Conclusion The adaptation process proved acceptable and feasible to both patients and staff. The co‐production methodology for the workbook and feedback from patients and staff was an effective way of iteratively refining the materials to ensure that they were both meaningful and acceptable to staff and patients. Subsequent work is required to develop the workbook and evaluate the feasibility of the intervention delivery, recruitment rates, uptake and adherence to the PSS using a randomised controlled trial. Patient or Public Contribution At each stage of the project consultation with patients and/or hospital staff was involved.